The Influence of Hedonic Lifestyle and Social Influence on Impulsive Online Purchases of Dahlia Brand Air Freshener Products - Ella Anastasya Sinambela (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
Human needs are increasing day by day. One of them is the need for air freshener. With the existence of online shopping media, it becomes easier for people to make purchases. In fact, people often make impulse purchases online. This research is to determine the influence of hedonic lifestyle and social influence in forming online impulse purchases. This research used 100 respondents with multiple linear regression analysis. The research results show that hedonic lifestyle and social influence influence the formation of online impulsive purchases.